Chemical leucoderma: Indian scenario, prognosis, and treatment - Bajaj A; Saraswat Abir; Srivastav P (Wolters Kluwer Medknow Publications, 2010)
Chemical leucoderma is an industrial disorder in developed countries and the common causative chemicals are phenols and catechols. Due to stringent controls and preventive measures the incidence has come down. In the recent past various chemicals in consumer products have also been documented to produce depigmentation.In India due to lax quality control measures chemical leucoderma due to consumer items is not uncommon.The various consumer items documented to cause contact depigmentation are sticker bindis,rain shoes,plastic chappals,hair dye/ black henna( kali mehndi), alta, wallets and even mobile plastic covers.